2012
DOI: 10.1039/c2jm31469j
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up assembly to Ag nanoparticles embedded Nb-doped TiO2 nanobulks with improved n-type thermoelectric properties

Abstract: Nb-doped TiO 2-based nanostructures were novelly prepared by an economical and environmentally friendly hydrothermal method from TiO 2 and Nb 2 O 5 powder precursors. The proposed formation mechanism is acceptable for the design of various Nb-doped TiO 2-based nanostructures. Furthermore, Nb-doped TiO 2 nanostructured bulk materials (nanobulks) embedded with Ag nanoinclusions were first fabricated by the bottom-up assembly of Ag 2 O nanoparticles loaded Nb-doped TiO 2-based nanostructures. The introduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Our results demonstrated that small amounts of Nb 2 O 5 does not affect the crystalline structures of the TiO 2 coatings as Nb is intercalated into the spaces between TiO 2 octahedron sheets during the coating process (solidication). [25][26][27] This intercalation resulted in shiing of the TiO 2 peaks to lower angles in the XRD pattern for the Nb 2 O 5 doped TiO 2 coatings (Fig. 1b and c).…”
Section: Discussionmentioning
confidence: 94%
“…Our results demonstrated that small amounts of Nb 2 O 5 does not affect the crystalline structures of the TiO 2 coatings as Nb is intercalated into the spaces between TiO 2 octahedron sheets during the coating process (solidication). [25][26][27] This intercalation resulted in shiing of the TiO 2 peaks to lower angles in the XRD pattern for the Nb 2 O 5 doped TiO 2 coatings (Fig. 1b and c).…”
Section: Discussionmentioning
confidence: 94%
“…[25][26][27][28][29] Non-stoichiometry and doping can lead to a high-ZT value because of the enhancement of the Seebeck coefficient and electrical conductivity. However, non-stoichiometric TiO x (1oxo2) materials exhibit low thermal conductivity at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xu et al 15 prepared Al-doped TiO2 nanostructured materials to increase the electrical conductivity and achieved an enhanced ZT of 0.091; Liu et al 16 reported that Ag-codoped TiO 2 nanostructured materials exhibit an enhanced ZT of 0.082 at 1073 K. In the past few decades, nanocomposites consisting of metal particles embedded in an insulating matrix have drawn great interest.…”
Section: Introductionmentioning
confidence: 99%